Fluoroscopic Assessment of Lumbar Total Disc Replacement Kinematics During Walking. Issue 7 (1st April 2015) - Barrett, Rod S.; Lichtwark, Glen A.; Armstrong, Codie; Barber, Lee; Scott-Young, Matthew; Hall, Richard M.
<x xml:space="preserve">Abstract</x> Study Design. Descriptive. Objective. The purpose of this study was to determine the in vivo kinematics of functional spinal units, during gait, in individuals with a single-level lumbar total disc replacement (TDR). Summary of Background Data. TDR is a motion preservation technology that offers an alternative to spinal fusion for treatment of degenerative disc disease. The aim of TDRs is to replicate motion of the functional spinal units, which may protect adjacent intervertebral discs against accelerated degeneration. At present, there is limited understanding of the in vivo motion of TDRs, particularly during dynamic activities such as gait. Such information is important for understanding the wear characteristics of TDRs and furthering design rationale of future implants. Methods. TDR motions were obtained from 24 participants who underwent implantation with single-level L4–L5 or L5–S1 CHARITÉ or In Motion TDRs. Video fluoroscopy was used to obtain measurements in the frontal and sagittal planes during fixed speed treadmill walking. Results. The mean range of motion between the upper and lower lumbar TDR endplates during walking was 1.6° and 2.4° in the frontal and sagittal planes, respectively. These values were significantly different from zero and corresponded to 19% of the maximum static range of motion in each plane. Conclusion. Lumbar TDRs provide a degree of motion preservation at the operative level during moderate speed walking. The distribution of lumbar TDR motions during walking presented here will inform relevant standards for conducting standardized tests of lumbar TDRs, particularly wear assessments, and, hence, enable more realistic mechanical and computer-based wear simulations to be performed. Level of Evidence: N/A